Importance of self-perception in relation to periodontal diseases (Research, Society and Development, 2024)
Oral health conditions are a factor that greatly interferes with the quality of life of individuals. Periodontal disease is caused by the interaction of periodontopathogenic microorganisms and abnormal immune responses in the gingival and periodontal tissues. Most adults have some manifestation of periodontal disease, which begins with gingivitis and can progress to periodontitis and eventual tooth loss. These consequences impact the quality of life of individuals in all dimensions, whether physical, functional, nutritional, or even psychosocial. The objective of this research was to assess, through a narrative review, the importance of patients' self-perception regarding their periodontal condition and to demonstrate the importance of guidance regarding oral health as a means of preventing and treating periodontal diseases. Scientific articles relevant to the proposed topic were analyzed on the Google Scholar, Scientific Electronic Library (Scielo), and PubMed platforms. The articles were screened by reading the title and abstract. The inclusion criteria were mostly national and international scientific articles using the following descriptors: “Periodontal disease”, “Oral health”, “Self-perception”. The selected studies met the criteria of complete publication and free access; incomplete or outdated studies were excluded. It is concluded that despite the high rates of periodontal diseases, many individuals do not have adequate knowledge about their periodontal condition. It is suggested that educational methods on oral health and the primary symptoms of periodontal disease be implemented using clearer and more explanatory methods.